Pengaruh Penambahan Ekstrak Daun dan Bubuk Teh, Kopi, dan Coklat Terhadap Fermentasi Nata De Coco - Merry Tri Indah Permata Sari; - Periadnadi; - Nurmiati (Universitas Andalas, 2014)
This study aimed of to find out the effect of leaf extract and seed powder containing alkaloid which occured on the production process of nata de coco. An experiment was conducted using Complete Randomized Design (CRD) with factorial pattern. The result showed that the brewed extract of tea, coffee, chocolate affected the weight product of nata de coco. The brewed extract of green tea showed the best result on weight of the nata (24.66 g) which has a significant difference from the treatments of black tea, coffee powder, cocoa powder, coffee leaf, and chocolate leaf. The best dose of brewed extract in obtaining nata was 2 g/100 ml.Keywords : alkaloid, nata de coco, effect.